On curvatures of a frenet curve in the pseudo - Galilean space - Ogrenmis, Alper Osman (Academic Journals, 2010)
In this paper, we study curvatures of a frenet curve in the pseudo-Galilean space and we obtain some characterizations.
Keywords: Pseudo-Galilean space; frenet curve; curvature